Study on the Characteristics and Applications of Coal Ash and Slag from Power Plant of Anhui Huaibei Mining Area - Zhang, Xianglin; Wang, Yun (Asian Journal of Chemistry, 2014)
In this study, the compositions and characteristics of circulating fluidized bed combustion (CFBC) desulfurization ash and desulfurization slag from the power plant of Anhui Huaibei Mining Area were analyzed. A kind of composite aluminosilicate cementitious material was prepared through mixing cement with desulfurization ash or desulfurization slag with higher activity ratio and performances in compressive and flexural strength were then tested. The results showed that when the content of desulfurization ash or desulfurization slag was 10 % (wt. %), the compressive and flexural strength were higher than those of the pure cement paste, but 30 % or more, significantly reduced. Moreover, compared to the pure cement paste, the compressive strength of cement paste added by 5 % of desulfurization slag and 5 % of fly ash was lower, but the long-term compressive strength was increased by 21 %.